External validation study of hip peri-prosthetic joint infection with cemented custom-made articulating spacer (CUMARS). Issue 3 (May 2022) - Quayle, Jonathan; Barakat, Ahmed; Klasan, Antonio; Mittal, Aaina; Stott, Philip
Introduction: Peri-prosthetic joint infection (PJI) is a devastating complication after total hip arthroplasty (THA). The use of custom-made articulating spacers (CUMARS) has been described for use in the first of 2-stage treatment. We report our outcomes of managing PJI using CUMARS. Methods: Patients undergoing 1st-stage revision using the Exeter standard stem, all-polyethylene acetabulum and antibiotic-loaded cement were identified. Medical records were assessed for demographics, microbiological and operative treatment, complications, eradication of infection and reoperations. No postoperative restrictions were enforced. 2nd-stage revision was undertaken in the presence of pain or subsidence. Results: 53 patients underwent 1st-stage revision using this technique. The average follow-up was 3.9 (range 0.5–7.2) years. Infection was eradicated in 47 (88.7%) patients. 2 patients had chronic infection managed with suppressive antibiotics, 2 patients died before eradication confirmed, 1 patient had raised inflammatory markers but no positive aspiration cultures, 1 patient was lost to follow-up. Complications occurred in 5 (9.4%) patients – 4 dislocations and 1 infected haematoma. 4 patients required a repeated 1st stage. 2nd-stage revision was performed in 19 patients (35%). Conclusions: The CUMARS technique is an effective way of eradicating PJI after THA. It maintains function by providing a stable construct that permits weight-bearing. It delays or negates the need for 2nd-stage revision. Furthermore, it allows surgeons to choose between managing patients prospectively as a single-stage revision with the option of reverting to a 2nd stage.